Book‐shaped decellularized tendon matrix scaffold combined with bone marrow mesenchymal stem cells‐sheets for repair of achilles tendon defect in rabbit. Issue 4 (28th March 2019) - Xie, Shanshan; Zhou, Yongchun; Tang, Yifu; Chen, Can; Li, Shengcan; Zhao, Chunfeng; Hu, Jianzhong; Lu, Hongbin
ABSTRACT: Tissue‐engineering approaches have great potential to improve the treatment of tendon injuries which are major musculoskeletal disorders. The purpose of this study was to assess the tissue engineering potential of a novel multilayered decellularized tendon "book" scaffold with bone marrow mesenchymal stem cells (BMSCs) sheets for repair of an Achilles tendon defect in a rabbit model. In this study, we developed a novel book‐shaped decellularized scaffold derived from the extracellular matrix of tendon tissues from New Zealand white rabbits. Hematoxylin and eosin (H&E) staining, 4′, 6‐diamidino‐2‐phenylindole (DAPI) staining, DNA quantitation, and scanning electron microscopy (SEM) confirmed the efficiency of decellularization. After culturing BMSCs on decellularized scaffolds, 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay, SEM, quantitative real time polymerase chain reaction (qRT‐PCR), and immunofluorescence analysis demonstrated that decellularized scaffolds have the capacity to yield homogeneous distribution and alignment of BMSCs, as well as support their differentiation into tendon. Tenomodulin and Alpha‐1 collagen type I are important indicators for evaluating tenogenic differentiation of BMSCs. When decellularized "book" scaffolds with BMSCs sheets were used to repair a 1 mm Achilles tendon defect, histomorphological analysis, immunohistochemical assessment, and biomechanical testing showed that the book‐shaped decellularized tendon matrix scaffold and BMSCs sheets could promote the regeneration of type I collagen at the wound site during healing, and improve the mechanical properties of the repaired tendon. Therefore, the results of this study suggest that the novel decellularized "book" tendon scaffolds combined with BMSCs sheets have therapeutic effects on improving the healing quality of the Achilles tendon. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 9999:1–11, 2019.